2010
DOI: 10.1097/hjh.0b013e328336ecf3
|View full text |Cite
|
Sign up to set email alerts
|

A statistical investigation into the sharing of common genetic factors between blood pressure and obesity phenotypes in nuclear families from the Greater Bilbao (Spain)

Abstract: Blood pressure and obesity phenotypes do not share, in general, a substantial influence of common genetic and environmental effects. Finally, the results obtained revealed the importance of the amount of adipose tissue in the genetic correlations with SBP, DBP and MAP, at least, during the growth period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…In addition to the studies using twin data, there are studies estimating heritability using nuclear families, including also children. In population-based Portuguese (22) and Spanish family studies (23) and in a study including Hispanic US families enriched for childhood obesity (24), much lower heritability estimates were found for the metabolic traits than found in our study. This is, however, a common finding in non-twin family studies and is probably because of the fact that somewhat different sets of genes affect the metabolic factors at different ages, as well demonstrated for BMI from childhood to adulthood (14).…”
Section: Discussioncontrasting
confidence: 92%
“…In addition to the studies using twin data, there are studies estimating heritability using nuclear families, including also children. In population-based Portuguese (22) and Spanish family studies (23) and in a study including Hispanic US families enriched for childhood obesity (24), much lower heritability estimates were found for the metabolic traits than found in our study. This is, however, a common finding in non-twin family studies and is probably because of the fact that somewhat different sets of genes affect the metabolic factors at different ages, as well demonstrated for BMI from childhood to adulthood (14).…”
Section: Discussioncontrasting
confidence: 92%
“…The details of the study design and data collection of this crosssectional sample have been reported previously (Jelenkovic et al, 2010(Jelenkovic et al, , 2011. Briefly, the original sample involved 533 nuclear families assessed in education centres from the Greater Bilbao area (Basque Country, Spain) during two academic years (2006-2007 and 2007-2008).…”
Section: Study Samplementioning
confidence: 99%
“…Anthropometric somatotype was calculated according to formulae described in Carter and Heath (1990). Systolic (SBP) and diastolic blood pressure (DBP) were measured twice on the left arm of each participant with the Omron M6 (HEM-7001-E) digital device using three different cuff sizes (small, medium and large), as described in Jelenkovic et al (2010). Only children aged !4 years were measured for blood pressure.…”
Section: Anthropometric Dimensions and Blood Pressurementioning
confidence: 99%
“…Besides the above environmental factors, PP is related to genetic factors. Genetic epidemiological studies using families or twins have reported a series of data on the heritability estimates of PP, ranging from 0.11 [9] in black African families to 0.63 [10] in Swedish families [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Among them, a study of Chinese twins displayed that the heritability estimate is 0.45 [11], which is similar to Polish (0.37) [12] and American (0.51) [21] studies using family data, respectively.…”
Section: Introductionmentioning
confidence: 91%